Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.2131/jts.35.653
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pulmonary fibrosis by methotrexate treatment in mice lung in vivo and in vitro

Abstract: -Methotrexate (MTX) has been used as the first-line disease-modifying antirheumatic drug (DMARD) in patients with early progressive rheumatoid arthritis (RA). Several severe side effects such as myelosuppression, hepato-, nephro-, and pulmonary toxicities have been reported. However, the pathogenic mechanism of MTX-induced pulmonary fibrosis is still unknown. Here, we evaluated the morphological and biological changes of the pulmonary fibrosis in mice treated with MTX. Three, four and five weeks after consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 36 publications
(36 reference statements)
2
54
0
2
Order By: Relevance
“…We have previously reported that hyperplasia of interstitial tissues was observed in the alveolar septa and the increase of collagen content in the alveolar wall and fibrosis area after consecutive administration of MTX for 35 days (Ohbayashi et al, 2010). In addition, we have also revealed that the E-cadherin (epithelial cell marker) is significantly detected, whereas α-SMA (mesenchymal marker) is faintly observed in the alveolar septa and, which is restricted to vascular smooth muscle cells in control mice.…”
Section: Immunohistochemical Analyses For the Expression Of E-cadherimentioning
confidence: 62%
See 2 more Smart Citations
“…We have previously reported that hyperplasia of interstitial tissues was observed in the alveolar septa and the increase of collagen content in the alveolar wall and fibrosis area after consecutive administration of MTX for 35 days (Ohbayashi et al, 2010). In addition, we have also revealed that the E-cadherin (epithelial cell marker) is significantly detected, whereas α-SMA (mesenchymal marker) is faintly observed in the alveolar septa and, which is restricted to vascular smooth muscle cells in control mice.…”
Section: Immunohistochemical Analyses For the Expression Of E-cadherimentioning
confidence: 62%
“…Primary cell culture of lung fibroblasts was achieved using the protocol described previously (Ohbayashi et al, 2010). Briefly, the lungs removed from mice were minced into pieces of 2-3 mm 3 , agitated, and digested enzy-matically for 80 min at 37°C.…”
Section: Preparation Of Lung Alveolar Epithelial and Fibroblast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then 5-mm slices were cut and stained with hematoxylin and eosin following deparaffinization. Different histologic staining was used according to the tissue sources, for example, azan for collagen staining in the lung (28), and PAS for basement membrane staining in the kidney were performed (29). Then the tumor tissues were stained overnight with antibodies directed against Ki-67 (Novus Biologicals) and CREB (Cell Signaling Technology), using suitable secondary antibodies (SignalStain Boost IHC Detection Reagent; Cell Signaling Technology) in combination with diaminobenzidine (Applichem) as a substrate and counterstained with methylene blue.…”
Section: Patient Selection and Tissue Microarraysmentioning
confidence: 99%
“…In many studies, OH-P levels were measured to assess wound healing and fibrosis (1,16,17). In the study by O'Sullivan et al (18), higher OH-P levels were observed in subjects showing improved wound healing.…”
Section: Discussionmentioning
confidence: 99%